GAMBARAN PEMAHAMAN TEORI PSIKOANALISIS DAN IMPLIKASINYA DALAM PENDIDIKAN PADA MATA KULIAH KARAKTERISTIK DAN KOMPETENSI USIA DEWASA PADA MAHASISWA BIMBINGAN DAN KONSELING FKIP UNTIRTA - Putri Dian Dia Conia; Meitami Sofiyanti (Universitas Bina Bangsa, 2021)
One of the important materials for guidance and counseling students to learn in the Adult Age Characteristics and Competencies course is the understanding of personality theory in adulthood. One of the personality theory figures, Sigmund Freud, is the initiator of the Psychoanalytic theory, which is a theory that seeks to explain the nature and development of the human personality. Students who are already in the early adult age category, namely the age of 18 years and over, can also understand more about each other's personality by studying personality theory more deeply. The personality theory expressed by Sigmund Freud is also mandatory for students to study because it has implications for the field of education. Based on this, it is important for students who teach the Characteristics and Competencies of Adult Age courses to know more clearly about the description of personality understanding based on the Psychoanalytic theory of Sigmund Freud. The research method used is descriptive quantitative with a non-test instrument, namely interviews. Interviews were conducted with 5 students at 3rd semester majoring in Guidance and Counseling FKIP Sultan Ageng Tirtayasa University